Transfer of Land Ownership Through Frant with The Guaranteed Object - Siti Ayu Rahayu; Honainah Honainah; Nur Fitriah; Bhim Prakoso; Ainun Najib (Faculty of Law, University of Merdeka Malang, 2023)
This study aims to analyze how the concept of transferring land ownership rights through grants and how land status is obtained through grants, but the object remains a mortgage object. This article uses normative legal research methods. The sources of legal materials used are primary legal materials and secondary legal materials. The procedure for collecting legal materials in this article is to study library materials. Analysis of legal material sources was carried out descriptively. The results of the study concluded that the transfer of ownership rights to land due to grants can only be registered if the PPAT makes a deed. The contents and procedures for drawing up a deed are regulated in the Regulation of the Minister of Agrarian Affairs/Head of BPN No.3 of 1997. For the transfer of ownership rights to land through a grant, a PPAT deed cannot be made because the object of the grant deed is still an object of mortgage rights. To anticipate that grants can still be made, a grant-binding agreement was made before a Notary in order to fulfill legal protection for the parties.How to cite item: Rahayu, Siti Ayu, Honainah, Nur Fitriah, Bhim Prakoso, and Ainun Najib. â€œTransfer of Land Ownership Through Frant with The Guaranteed Object.â€ Jurnal Cakrawala Hukum. 14 no. 1 (2023): 63-75. DOI: 10.26905/idjch.v14i1.10005.